Future research focus and trends in nerve transplantation: a bibliometrics research from 2015 to 2024 - Sheng Wang; Jiajia Lu; Hui Han; Yongchuan Li; Nan Lu; Aimin Chen (Frontiers in Neurology)
BackgroundNerve transplantation, as a classical nerve repair technique, has received extensive attention in recent years. However, the rapid development of this field has also brought challenges such as knowledge fragmentation and the blurring of research hotspots. Therefore, at present, the future research direction of this field is not clear. Through the research method of bibliometrics, this study investigates the research hotspots and development trends in this field, and fills the research gap in this field.MethodsThe publications in the core database of Web of Science (WoS) were collected, and the included publications were analyzed by bibliometric methods after the screening exclusion process. The basic information of the publications was analyzed, and the future development direction and research hotspots were predicted and visualized.ResultsA total of 847 publications were included in the research, in the past 10 years, the number of publications in this field has nearly doubled (49 publications), and the number of publications in this field will continue to grow in the next 15 years. In terms of national contribution, the United States is the largest contributor (289 publications), and in terms of institutional contribution, Fudan University is the largest contributor (47 publications).ConclusionThis is the first bibliometric analysis in the field of nerve transplantation, which included all publications in this field in the past decade. Our results illuminate the contributions of countries and institutions, international cooperation, interdisciplinary relationships, and future research directions. This research will point out the future development path of nerve transplantation.